Dimensions of a healthy lifestyle among early adolescents: The simultaneous contribution of spirituality and family cohesiveness. - Mahensa, Iqnes Restual; Kinanthi, Melok Roro; Febriani, Zulfa (Universitas Muhammadiyah Surakarta, 2022)
Abstract. Early adolescents are prone to develop an unhealthy lifestyle. Along with personal factors, the microsystem’s environment can influence individual development. This study aims to examine whether a personal factor (spirituality) and a microsystem factor (family cohesiveness) simultaneously contribute significantly to a healthy lifestyle among early adolescents. A quantitative approach was applied in thisstudy, involving 166 participants in Jakarta, selected by convenience sampling. Health Promoting Lifestyle Profile II (Cronbach’s alpha = 0.800 - 0.840), the Brief Multidimensional Measure of Religiousness/ Spirituality (Cronbach’s alpha = 0.725), and the Brief Family Relationship Scale (BFRS) – cohesiveness dimension (Cronbach’s alpha = 0.934) were employed to collect data. Multiple regression analysis revealed that spirituality and family cohesiveness simultaneously contributed significantly to the healthy lifestyle of early adolescents, with a contribution of 6.1% to 30.9%. Thus, concurrently individual and family based approaches should be considered in designing interventions to promote a healthy lifestyle in early adolescents. Keywords: healthy lifestyle; spirituality; family cohesiveness.